2017
DOI: 10.1080/21505594.2016.1278337
|View full text |Cite
|
Sign up to set email alerts
|

M-ficolin is present in Aspergillus fumigatus infected lung and modulates epithelial cell immune responses elicited by fungal cell wall polysaccharides

Abstract: View related articles View Crossmark data Citing articles: 12 View citing articles LETTER TO THE EDITOR M-ficolin is present in Aspergillus fumigatus infected lung and modulates epithelial cell immune responses elicited by fungal cell wall polysaccharides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In this model, an increased fungal burden was observed in the double-deficient mice compared to WT animals at early times (i.e., 24 h) from infection, consistent with impaired opsonophagocytosis of dormant conidia [67]. Complement activation and recruitment of inflammatory cells were both unaltered in this setting; however, decreased production of proinflammatory cytokines in the lung of ficolin-A-and ficolin-B-deficient mice was reported, which suggests an early immunomodulatory role for these ficolins in vivo, similar to what described in vitro [62].…”
Section: The Complement In Animal Models Of Aspergillosissupporting
confidence: 82%
See 2 more Smart Citations
“…In this model, an increased fungal burden was observed in the double-deficient mice compared to WT animals at early times (i.e., 24 h) from infection, consistent with impaired opsonophagocytosis of dormant conidia [67]. Complement activation and recruitment of inflammatory cells were both unaltered in this setting; however, decreased production of proinflammatory cytokines in the lung of ficolin-A-and ficolin-B-deficient mice was reported, which suggests an early immunomodulatory role for these ficolins in vivo, similar to what described in vitro [62].…”
Section: The Complement In Animal Models Of Aspergillosissupporting
confidence: 82%
“…As opposed to a-glucans, chitin, the innermost polysaccharide of the fungal cell wall, has been proposed as a ligand of ficolins. In this regard, ficolin-1 recognized chitin (in addition to b-glucans) on the surface of A. fumigatus young hyphae [62], and the binding of ficolins 2 and 3 (and murine ficolin-A) to A. fumigatus conidia was inhibited by N-acetylglucosamine (GlcNAc, the monosaccharide component of chitin), suggesting that they may recognize chitin and exert complement activating functions on germlings and hyphae (in addition to conidia) [67]. The relevance of chitin as a PAMP for complement activation has been recently highlighted in a study on mutant strains of A. fumigatus lacking b-glucans, which synthesized and exposed high levels of chitin (likely through compensatory pathways), and underwent enhanced complement activation and dendritic cell-mediated clearance [68].…”
Section: Pathways Of Complement Activation Along the Fungal Life Cyclementioning
confidence: 98%
See 1 more Smart Citation
“…The crystal structure of FIBCD1-FReD ( 16 ) is homologous to FReD superfamily members involved in immune regulation, including ficolin-1 and −2 ( 17 , 18 ). Both ficolin-1 and −2 recognize A. fumigatus -associated PAMPs ( 19 , 20 ) and binds directly or indirectly to resting A. fumigatus conidia ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Borger and colleagues have reported an up-regulation of gene transcription by Aspergillus fumigatus proteases as cause of increased release of IL-6 and IL-8 by A549 pulmonary epithelial cells and primary epithelial cells 39. More recent studies have shown that in vitro opsonisation of A. fumigatus conidia with H-ficolin,40 L-ficolin23 and M-ficolin,41 which play essential roles in pathogen recognition and complement activation through T A B L E 3 Performance of cytokine levels in serum and bronchoalveolar fluid (BALF) for differentiating cases with probable/proven IPA (n = 10) from matched controls (n = 20)…”
mentioning
confidence: 99%